THE PRACTICAL SIGNIFICANCE AND FUNCTIONAL ROLE OF FOREIGN LANGUAGE IN TRANSPORT-LOGISTICS EDUCATION - Mamajanova G‘uncha Xemrayevna; Shakirova Saida Tukhtajonovna (Western European Studies, 2026)
This article analyzes the practical significance and functional role of foreign language in the transport-logistics education system. Within the framework of the research, the role of foreign language in professional communication, terminological precision, and the formation of professional competencies is highlighted. Based on the English for Specific Purposes (ESP) approach, the integrative functions of foreign language in the transportlogistics field are identified, and its effectiveness in the professional education process is theoretically substantiated. The research results demonstrate that organizing foreign language instruction adapted to transport-logistics education increases specialists' competitiveness in the international labor market.
Keywords: transport-logistics education; foreign language; ESP